2006
DOI: 10.1103/physrevb.73.045426
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects on magneto-oscillations in a two-dimensional electron gas

Abstract: Motivated by recent experiments, we study the interaction corrections to the damping of magnetooscillations in a two-dimensional electron gas (2DEG). We identify leading contributions to the interaction-induced damping which are induced by corrections to the effective mass and quantum scattering time. The damping factor is calculated for Coulomb and short-range interaction in the whole range of temperatures, from the ballistic to the diffusive regime. It is shown that the dominant effect is that of the renorma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 57 publications
3
60
0
1
Order By: Relevance
“…We then analyzed our data including the T -dependence of R 0 and assuming that the relative T -dependence of τ q is equal to half the relative T -dependence of R 0 . 26,42 We found that these two different methods yield very similar values for m * within our error bar range (∼ 10%), thus here we only report m * values deduced by assuming that both R 0 and τ q are T -independent. …”
Section: Sample Parameters and Experimental Detailsmentioning
confidence: 62%
“…We then analyzed our data including the T -dependence of R 0 and assuming that the relative T -dependence of τ q is equal to half the relative T -dependence of R 0 . 26,42 We found that these two different methods yield very similar values for m * within our error bar range (∼ 10%), thus here we only report m * values deduced by assuming that both R 0 and τ q are T -independent. …”
Section: Sample Parameters and Experimental Detailsmentioning
confidence: 62%
“…For classically weak perpendicular magnetic field, modification of the Lifshitz-Kosevich-type expression for a 2D electron interacting disordered system has been studied in Refs. [24,25].…”
mentioning
confidence: 99%
“…[64]. In addition to experimental motivation related to the apparent metal-insulator transition in two-dimensional systems, the corresponding theory complements the recently developed theory of interaction effects in transport of 2D electrons in zero and non-quantizing magnetic fields [55,56].…”
Section: Interaction Effects On Oscillationsmentioning
confidence: 87%